Analysis of The Influence of Selebgram Bali on Interest in Guest Visits at Sanctoo Suites and Villas - Rinayanthi, Ni Made; Nirmalasari, Ni Luh Putu Intan (Jurnal Manajemen Pelayanan Hotel, 2023)
This study discusses the influence of the promotion carried out by celebrity Anggia Kloer in promoting facilities and events that will be held through the program with the aim of increasing consumer confidence in Manado so that it can be recognized by many people. The purpose of this study is to find out whether visibility, credibility, attraction, power have a positive and significant effect on the interest in visiting guests at the Four Points by Sanctoo Suites and Villas hotel. The population in this study were guests who had stayed at Four Points By Sanctoo Suites and Villas, had Instagram and followed Anggia Kloer on Instagram. The sample of this research is 40 people. The research data was obtained by distributing questionnaires online using Google Forms to respondents. The static analysis technique used is multiple linear regression, validity test, reliability test, t test, and f test. Keywords: celebrity, promotions , guest visits, visibility, credibility, attraction , power